ANALISIS PERBANDINGAN ALGORITMA LEMPEL ZIV WELCH DAN TABOO CODES DALAM KOMPRESI FILE MKV - Ridho, Faisal; Pristiwanto; Siregar, Saidi Ramadan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
When selecting the most efficient compression method, it is crucial to compare the available algorithms. The methods used for file compression vary, including algorithms such as LZW (Lempel Ziv Welch) and Taboo Codes. Large file sizes can cause various issues, such as increased storage requirements and longer transmission times, leading to higher costs. Compression is essential as it reduces file size, and different compression algorithms, like LZW and Taboo Codes, offer various benefits. Both algorithms are lossless compression techniques. The criteria used to determine which algorithm is more efficient for compressing MKV files include Compression Ratio, Ratio Compression, Redundancy, and Space Saving. The Exponential Method is used to analyze and compare these algorithms to understand their effectiveness, highlighting their respective strengths and weaknesses. After weighting each criterion using the exponential method, Lempel Ziv Welch achieved a score of 8.7926, while Taboo Codes achieved a score of 9.48313. Based on these results, it can be concluded that Lempel Ziv Welch requires less effort compared to Taboo Codes.